THE INFLUENCE OF INDEPENDENT LEARNING ON THE ABILITY TO WRITE EXPOSITION TEXTS IN CLASS X - Hendarsyah Hendarsyah; Heris Hendriana; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2022)
This research was motivated by the writer's curiosity about the effect of independent learning on writing skills. The hypothesis to be tested is the influence of independent learning on the ability to write expository texts. This study uses a quantitative descriptive method because the research data is in the form of numbers, analyzed using statistics that connect between variables. The number of samples was 32 students of class X SMK PP Negeri Sumedang. The instruments used are test and non-test. The test instrument is in the form of an Exposition text writing skill test using Quizziz. The non-test instrument was in the form of a questionnaire containing 15 indicators of student learning independence including dependence, self-confidence, discipline, responsibility, and self-control. The result of correlation analysis is 0.414 proves that there is a close relationship between learning independence and the ability to write exposition texts. The regression value of r square is 0.797. This shows a significant effect between the independent variables on the dependent variable. As for the significance test of the regression coefficient obtained sig. 0.000 < 0.05 and t count = 11,566. This means that there is a significant influence between learning independence on the ability to write expository texts